Socio-Economic Effects of HIV/AIDS on Households with People Living With HIV/AIDS in Northern Nigeria - et. al., Suleiman Mohammed Saeed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to review the socio-economic effects of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) on households with People Living with HIV/AIDS (PLWHA) in Northern Nigeria. The pandemic is devastating and constitutes a serious threat to the socio-economic development of infected, affected, and society at large. This study was qualitative in nature, thus it utilized in-depth interviews to pull together information from the 39 key informants as its method. It is observed that HIV/AIDS occurrence rate has led to poor health, loss of jobs, and a high rate of labour reduction in all sectors, and this has contributed to the tremendous decline of the economy. This study discovered that increased expenses of households with PLWHA on financing funerals, healthcare, and other medical expenditures with decreased investment. Children emerging as head of the households and tasks of caring for orphans are increasingly inconsistent with many other studies. The pandemic has been a serious threat to the social and economic interests and survival of the households with PLWHA and their members. Many lives are lost due to the pandemic. The worst affected group is young people in their productive ages and by implication affects the socio-economic development of PLWHA, their households, and society at large. Thus, households with PLWHA experience numerous forms of stigma and prejudice together with human rights abuse that is detrimental to the total well-being of PLWHA. The dimensions of the stigma can be classified as internalized, community, and social-based. The patterns of managing the challenges of HIV/AIDS-related stigma adopted from the experience of households with PLWHA adopted include isolation, non-disclosure, and loss of follow-up as well as migration. The paper suggested that the government should come up with policies that can take care and support the socio-economic activities of households with PLWHA and also need to introduce policies and procedures for the reduction of stigma and discrimination against households with PLWHA and its members living with the epidemic. Households with PLWHA need to be assisted with medication subsidies to reduce medical expenses and stress on the households’ capitals among other recommendations.